Modified thermosetting phenolic resin, preparation method thereof and modified thermosetting phenolic resin product
By introducing liquid nitrile rubber, rare earth oxides and rigid oxide fillers into the phenolic resin, the modified thermoset phenolic resin is solved, and the defects and porosity of the phenolic resin during the high-temperature curing process is significantly improved and its mechanical properties are significantly improved. Tough, suitable for high-performance composite materials and wear-resistant and compressive applications.
Patent Information
- Application Number
- CN202411203894.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
AI Technical Summary
Phenolic resins are prone to defects and high porosity during high temperature curing, resulting in insufficient brittleness and mechanical properties, limiting their application in a wider range of fields.
Use liquid nitrile rubber and rare earth oxides and rigid oxide fillers to improve the toughness and mechanical strength of the resin through island-like structure and good compatibility, and reduce curing defects through rare earth elements to form low porosity and high Properties of modified thermosetting phenolic resin.
The impact strength, tensile strength, compression strength and friction properties of phenolic resin have been significantly improved, and the porosity has been greatly reduced, and its performance is close to that of metal cast iron, which has broadened its application in machinery, automobiles and other fields.
Smart Images

Figure CN119192770A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenolic resins, and in particular to a modified thermosetting phenolic resin and a preparation method thereof, and a modified thermosetting phenolic resin product. Background Art
[0002] Phenolic resin is one of the most widely used thermosetting plastics in industry. It has been widely used since the early 20th century due to its excellent fire resistance, high mechanical strength and low cost. This resin plays an important role in many fields such as electrical insulation, molded products, coatings and adhesives. However, due to the inherent characteristics of its molecular structure, it is brittle and has a high porosity. It is easy to form internal microcracks during the manufacturing process, which restricts its application in a wider range of fields.
[0003] The brittleness of phenolic resin mainly comes from the interconnection of rigid aromatic units in its structure through methylene bonds. During the heat treatment process, the resin undergoes a condensation reaction, and as the temperature rises, volatile substances such as moisture and formaldehyde are produced. The release of these volatile substances often produces microscopic defects such as holes and cracks inside the resin, which become the source of stress concentration when the material is loaded, thereby exacerbating the brittle failure of the material. Although the use of flexible materials such as rubber for modification can improve the toughness of phenolic resin to a certain extent, this single modification method often sacrifices other properties of the resin. Therefore, the industry has an urgent need for a composite modification technology that can simultaneously improve the toughness and strength of phenolic resin and reduce porosity and defects inside the resin. Summary of the invention
[0004] The object of the present invention is to provide a modified thermosetting phenolic resin and a preparation method thereof, and a modified thermosetting phenolic resin product. The modified thermosetting phenolic resin provided by the present invention has high toughness, high overall mechanical strength, low porosity and low defects.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a modified thermosetting phenolic resin, which comprises the following raw materials, measured by weight: 100 parts of thermosetting phenolic resin, 10 to 50 parts of liquid nitrile rubber, 1 to 30 parts of rare earth oxide and 1 to 30 parts of rigid oxide filler;
[0007] The rigid oxide filler is one or more of silicon dioxide, titanium dioxide and zirconium dioxide.
[0008] Preferably, the liquid nitrile rubber is carboxyl-terminated liquid nitrile rubber, amine-terminated liquid nitrile rubber or vinyl-terminated liquid nitrile rubber.
[0009] Preferably, the acrylonitrile content of the liquid nitrile rubber is 5 to 50 wt %.
[0010] Preferably, the rare earth oxide is one or more of cerium oxide, praseodymium oxide, lanthanum oxide, europium oxide, lutetium oxide, ytterbium oxide, thulium oxide, dysprosium oxide, scandium oxide, yttrium oxide, erbium oxide, gadolinium oxide, holmium oxide, neodymium oxide, samarium oxide and terbium oxide.
[0011] Preferably, the particle size of the rare earth oxide is 10 nm to 100 μm.
[0012] Preferably, the particle size of the rigid oxide filler is 10 nm to 10 μm.
[0013] The present invention provides a method for preparing the modified thermosetting phenolic resin of the above scheme, comprising the following steps: heating the thermosetting phenolic resin and the liquid nitrile rubber respectively to obtain a low-viscosity phenolic resin and a low-viscosity liquid nitrile rubber respectively;
[0014] The low-viscosity phenolic resin, low-viscosity liquid nitrile rubber, rare earth oxide and rigid oxide filler are mixed to obtain the modified thermosetting phenolic resin.
[0015] Preferably, the viscosity of the low-viscosity phenolic resin is 100-500 cp; the viscosity of the low-viscosity nitrile rubber is 500-1000 cp.
[0016] Preferably, the mixing comprises: adding the low-viscosity liquid nitrile rubber to a low-viscosity phenolic resin, adding rare earth oxides and rigid oxide fillers to the resulting mixed system, mixing using a high-speed homogenizing and dispersing emulsifier, and then stirring the resulting mixture at 100-150°C.
[0017] The present invention provides a modified thermosetting phenolic resin product, which is obtained by curing the modified thermosetting phenolic resin described in the above scheme or the modified thermosetting phenolic resin prepared by the preparation method described in the above scheme.
[0018] The present invention provides a modified thermosetting phenolic resin, which comprises the following raw materials by weight: 100 parts of thermosetting phenolic resin, 10 to 50 parts of liquid nitrile rubber, 1 to 30 parts of rare earth oxides and 1 to 30 parts of rigid oxide fillers; the rigid oxide fillers are one or more of silicon dioxide, titanium dioxide and zirconium dioxide. The present invention not only optimizes the fracture toughness of the resin, but also improves its overall mechanical strength by introducing a specific proportion of soft (referring to liquid nitrile rubber) and rigid particles (referring to rare earth oxides and rigid oxide fillers), the porosity of the product is greatly reduced, and the excellent compressive and friction properties broaden its application field, so that it can be used in wear resistance and pressure resistance, such as machinery, automobiles, ships and other fields. Specifically:
[0019] The improvement of its mechanical properties is due to the precipitation of liquid rubber in phenolic resin to form an island-like structure, which can significantly improve the impact strength, tensile strength, compression strength and friction performance of phenolic resin. Secondly, liquid nitrile rubber, rare earth oxides, and rigid oxide particles have good compatibility with phenolic resin and high bonding strength with the resin matrix, which can significantly improve the mechanical properties. For achieving low porosity and high performance, firstly, rare earth elements have unique electronic orbits and valence states, which can affect the curing of phenolic resin and reduce defects; secondly, the addition of an appropriate amount of liquid nitrile rubber and uniform stirring form small and evenly distributed rubber particles, which can disperse and absorb the internal stress generated by phenolic resin during the curing process and reduce internal defects.
[0020] The present invention not only effectively solves the problems of defects and high porosity that traditional phenolic resins are prone to during high-temperature curing, but also achieves all-round optimization of mechanical properties through a multi-component composite modification technology. The modified thermosetting phenolic resin of the present invention not only has excellent mechanical properties, but also exhibits high toughness; compared with ordinary thermosetting phenolic resins (PF-602), the compression strength and compression deformation are increased by 87.08% and 110.88% respectively, the compression strength is 6.81 times the tensile strength, and the compression performance is similar to that of metal cast iron. The present invention greatly improves the practicality and economic value of phenolic resins, and provides broad prospects for their application in high-performance composite materials, aerospace, automobile manufacturing and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a physical picture of the impact test piece prepared in Example 1;
[0022] Figure 2 This is a fracture morphology diagram of the impact specimen prepared in Example 1;
[0023] Figure 3 This is a physical picture of the impact test piece prepared in Example 2;
[0024] Figure 4 This is a fracture morphology diagram of the impact specimen prepared in Example 2;
[0025] Figure 5 This is a physical picture of the impact test piece prepared in Example 3;
[0026] Figure 6 This is a fracture morphology diagram of the impact specimen prepared in Example 3;
[0027] Figure 7 This is a physical picture of the impact test piece prepared in Example 4;
[0028] Figure 8This is a fracture morphology diagram of the impact specimen prepared in Example 4;
[0029] Fig. 9 This is a physical picture of the tensile test piece prepared in Example 5;
[0030] Fig.10 This is a fracture morphology diagram of the tensile test piece prepared in Example 5;
[0031] Fig.11 This is a physical picture of the compression test piece prepared in Example 6;
[0032] Fig.12 This is a fracture morphology image of the compression specimen prepared in Example 6;
[0033] Fig.13 This is a physical picture of the impact test piece prepared in Comparative Example 1;
[0034] Fig.14 This is a fracture morphology diagram of the impact specimen prepared in Comparative Example 1;
[0035] Fig.15 This is a physical picture of the tensile test piece prepared in Comparative Example 2;
[0036] Fig.16 This is a fracture morphology diagram of the tensile test piece prepared in Comparative Example 2;
[0037] Fig.17 This is a physical picture of the compression specimen prepared in Comparative Example 3;
[0038] Fig.18 This is a fracture morphology diagram of the compression specimen prepared in Comparative Example 3;
[0039] Fig.19 This is a physical picture of the impact test piece prepared in Comparative Example 4;
[0040] Fig. 20 This is a fracture morphology diagram of the impact specimen prepared in Comparative Example 4;
[0041] Fig.21 This is a physical picture of the impact test piece prepared in Comparative Example 5;
[0042] Fig. 22 This is the fracture morphology of the impact specimen prepared in Comparative Example 5. DETAILED DESCRIPTION
[0043] The invention provides a modified thermosetting phenolic resin, which comprises the following raw materials, measured by weight: 100 parts of thermosetting phenolic resin, 10 to 50 parts of liquid nitrile rubber, 1 to 30 parts of rare earth oxide and 1 to 30 parts of rigid oxide filler;
[0044] The rigid oxide filler is one or more of silicon dioxide, titanium dioxide and zirconium dioxide.
[0045] In the present invention, unless otherwise specified, the raw materials and equipment used are commercially available products well known in the art.
[0046] In parts by weight, the raw materials for preparing the modified thermosetting phenolic resin provided by the present invention include 100 parts of thermosetting phenolic resin (liquid at room temperature); in the present invention, the thermosetting phenolic resin is preferably thermosetting phenolic resin PF-602.
[0047] Based on the weight of the thermosetting phenolic resin, the raw material for preparing the modified phenolic resin provided by the present invention includes 10 to 50 parts of liquid nitrile rubber, which can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, which are not listed here. In the present invention, the liquid nitrile rubber is preferably a carboxyl-terminated liquid nitrile rubber, an amine-terminated liquid nitrile rubber or an olefin-terminated vinyl nitrile rubber; the acrylonitrile content of the liquid nitrile rubber is preferably 5 to 50wt%, which can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, which are not listed here. In the present invention, the liquid nitrile rubber precipitates in the phenolic resin matrix to form an island-like structure, which can significantly improve the impact strength, tensile strength, compression strength and friction performance of the phenolic resin; the present invention controls the amount of liquid nitrile rubber within a suitable range, which is conducive to forming uniformly distributed rubber particles, which can disperse and absorb the internal stress generated by the phenolic resin during the curing process and reduce internal defects.
[0048] Based on the weight of the thermosetting phenolic resin, the raw materials for preparing the modified phenolic resin provided by the present invention include 1 to 30 parts of rare earth oxide, preferably 5 to 25 parts, more preferably 10 to 20 parts, and more preferably 13 to 17 parts. In the present invention, the rare earth oxide is preferably one or more of cerium oxide, praseodymium oxide, lanthanum oxide, europium oxide, lutetium oxide, ytterbium oxide, thulium oxide, dysprosium oxide, scandium oxide, yttrium oxide, erbium oxide, gadolinium oxide, holmium oxide, neodymium oxide, samarium oxide and terbium oxide; the particle size of the rare earth oxide is preferably 10nm to 100μm, more preferably 1 to 90μm, and more preferably 10 to 80μm. In some embodiments of the present invention, it is specifically 50μm, 30μm, 60μm or 10μm. In the present invention, the rare earth oxide can be commercially available or homemade. In the embodiments of the present invention, it is obtained by laboratory homemade using a well-known method. In the present invention, the rare earth oxide has good compatibility with the phenolic resin matrix, which is beneficial to improving the mechanical properties of the phenolic resin. At the same time, the rare earth element has a unique electron orbit and valence state, which can affect the curing of the phenolic resin, thereby reducing defects.
[0049] Based on the weight of the thermosetting phenolic resin, the raw materials for preparing the modified phenolic resin provided by the present invention include 1 to 30 parts of rigid oxide fillers, preferably 5 to 25 parts, more preferably 10 to 20 parts, and more preferably 13 to 17 parts. In the present invention, the rigid oxide filler is one or more of silicon dioxide, titanium dioxide and zirconium dioxide; the particle size of the rigid oxide filler is preferably 10nm to 10μm, more preferably 20nm to 1μm; in some embodiments of the present invention, it is specifically 80nm, 100nm, 50nm or 20nm. In the present invention, the rigid oxide filler can further improve the toughness, mechanical properties and friction properties of the resin, and also contribute to the stability of thermal stability and stiffness.
[0050] The present invention provides a method for preparing the modified thermosetting phenolic resin of the above scheme, comprising the following steps: heating the thermosetting phenolic resin and liquid nitrile rubber respectively to obtain a low-viscosity phenolic resin and a low-viscosity liquid nitrile rubber;
[0051] The low-viscosity phenolic resin, low-viscosity liquid nitrile rubber, rare earth oxide and rigid oxide filler are mixed to obtain the modified thermosetting phenolic resin.
[0052] The thermosetting phenolic resin and the liquid nitrile rubber of the invention are heated separately to obtain low-viscosity phenolic resin and low-viscosity liquid nitrile rubber respectively.
[0053] In the present invention, the heating temperatures of the thermosetting phenolic resin and the liquid nitrile rubber are independently preferably 100-150° C. The present invention does not make any special requirements on the heating time, as long as the viscosity of the low-viscosity phenolic resin obtained after heating is 100-500 cp and the viscosity of the low-viscosity liquid nitrile rubber is 500-1000 cp.
[0054] After obtaining the low-viscosity phenolic resin and the low-viscosity liquid nitrile rubber, the present invention mixes the low-viscosity phenolic resin, the low-viscosity liquid nitrile rubber, rare earth oxides and rigid oxide fillers to obtain the modified thermosetting phenolic resin.
[0055] In the present invention, the mixing preferably includes: adding the low-viscosity liquid nitrile rubber to a low-viscosity phenolic resin, adding rare earth oxides and rigid oxide fillers to the resulting mixed system, mixing using a high-speed homogenizing and dispersing emulsifier, and then stirring the resulting mixture at 100-150°C.
[0056] In the present invention, the mixing speed of the high-speed homogenizing dispersing emulsifier is preferably 10000-20000 rpm, more preferably 12000-18000 rpm; the mixing time of the high-speed homogenizing dispersing emulsifier is preferably 10-30 min, more preferably 15-25 min. The present invention adopts a high-speed homogenizing dispersing emulsifier for mixing, which is conducive to more uniform dispersion of each component, thereby further reducing defects in the curing process.
[0057] In the present invention, the stirring rate is preferably 300-800 rpm, more preferably 400-700 rpm; the stirring time is preferably 30-90 min, more preferably 40-80 min. In the present invention, the stirring is preferably performed in an oil bath, so that the temperature is maintained at 100-150°C.
[0058] The present invention provides a modified thermosetting phenolic resin product, which is obtained by curing the modified thermosetting phenolic resin described in the above scheme.
[0059] The present invention preferably pours the modified thermosetting phenolic resin into a mold for curing and molding. The present invention can select a suitable mold according to the shape of the product. In an embodiment of the present invention, the modified thermosetting phenolic resin product is specifically an impact test piece, a compression test piece or a tensile test piece.
[0060] In the present invention, the curing molding conditions preferably include: curing at 100-130°C for 1-3h, curing at 140-160°C for 1-3h, and curing at 165-180°C for 2-4h; more preferably: curing at 130°C for 2h, curing at 150°C for 2h, and curing at 170°C for 2h.
[0061] After the curing and molding is completed, the present invention preferably cools the product to room temperature in the furnace to obtain the modified thermosetting phenolic resin product.
[0062] In the present invention, the test is carried out according to GB / T2567-2008 Test Method for Performance of Resin Castings. When the modified thermosetting phenolic resin is made into an impact test piece, the impact strength is 6.5-8.0 KJ·m -2 When the modified thermosetting phenolic resin is made into a tensile specimen, the tensile strength is 28.32-32.98 MPa, and the elongation at break is 2.98-3.65%; when the modified thermosetting phenolic resin is made into a compression specimen, the compressive strength is 209.53-224.50 MPa, and the compression deformation is 6.89-7.56 mm.
[0063] The modified thermosetting phenolic resin and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0064] The sources of raw materials used in the following examples and comparative examples are:
[0065] Phenolic resin, model PF-602, was commercially available; liquid nitrile rubber was purchased from Lanzhou Chemical Research Center of China National Petroleum Corporation; rare earth oxides were homemade in the laboratory; silicon dioxide, titanium dioxide and zirconium dioxide were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0066] Example 1
[0067] Preparation of impact test pieces
[0068] In parts by weight, 100 parts of phenolic resin; 30 parts of liquid nitrile rubber, 40wt% acrylonitrile content; 15 parts of cerium dioxide, 50μm particle size, 10 parts of silicon dioxide, 80nm particle size. The phenolic resin and liquid nitrile rubber are placed in a 130°C oven respectively, the phenolic resin is heated to a viscosity of 200cp, and the liquid nitrile rubber is heated to a viscosity of 800cp. The liquid rubber is added to the phenolic resin and mixed evenly, and cerium dioxide and silicon dioxide particles are gradually added, and a high-speed homogenizing and dispersing emulsifier is used for mixing, the speed is 12000rpm, and the mixture is stirred for 15min, and then stirred in an oil bath pot (140°C) for 75min (700rpm) to obtain a modified thermosetting phenolic resin.
[0069] Then the modified thermosetting phenolic resin was placed in the mold of a flat vulcanizer and cured by stepwise heating: 125℃ for 2h, 145℃ for 2h, and 165℃ for 2h, so that the modified thermosetting phenolic resin was crosslinked and cured to obtain an impact specimen. Figure 1As shown in the figure, a total of 5 impact specimens were prepared. The impact specimens were tested according to GB / T2567-2008 Test Method for Performance of Resin Castings, and the impact strength was 7.77KJ·m -2 The fracture morphology of one of the specimens is as follows Figure 2 As shown in the figure, the porosity of the specimens is greatly reduced.
[0070] Example 2
[0071] Preparation of impact test pieces
[0072] In parts by weight, 100 parts of phenolic resin; 25 parts of liquid nitrile rubber, 40wt% acrylonitrile content; 20 parts of lanthanum oxide, 30μm particle size, 20 parts of silicon dioxide, 100nm particle size. The phenolic resin and liquid nitrile rubber are placed in a 130°C oven respectively, the phenolic resin is heated to a viscosity of 300cp, and the liquid nitrile rubber is heated to a viscosity of 600cp. The liquid rubber is added to the phenolic resin and mixed evenly, lanthanum oxide and silicon dioxide particles are gradually added, mixed using a high-speed homogenizing and dispersing emulsifier (16000rpm), stirred for 20min, and then stirred in an oil bath (120°C) for 90min (700rpm) to obtain a modified thermosetting phenolic resin.
[0073] Then the modified thermosetting phenolic resin is placed in the mold of a flat vulcanizer and cured by step-by-step heating: 130°C for 3h, 145°C for 2.5h, and 180°C for 3.5h to crosslink and cure the modified thermosetting phenolic resin to obtain an impact specimen. Figure 3 shown.
[0074] The impact test piece was tested according to GB / T2567-2008 Test Method for Performance of Resin Castings, and the impact strength was 6.83KJ·m -2 , the fracture morphology is as follows Figure 4 As shown in the figure, the porosity of the specimens is greatly reduced.
[0075] Example 3
[0076] Preparation of impact test pieces
[0077] In parts by weight, 150 parts of phenolic resin; 40 parts of liquid nitrile rubber, 40wt% acrylonitrile content; 15 parts of europium oxide, particle size 60μm, 25 parts of silicon dioxide, particle size 50nm. The phenolic resin and liquid nitrile rubber are placed in a 130°C oven respectively, the phenolic resin is heated to a viscosity of 200cp, and the liquid nitrile rubber is heated to a viscosity of 500cp. The liquid rubber is added to the phenolic resin and mixed evenly, europium oxide and silicon dioxide particles are gradually added, and a high-speed homogenizing and dispersing emulsifier is used for mixing (17000rpm), stirring for 25min, and then stirring in an oil bath pot (135°C) for 80min (600rpm) to obtain a modified thermosetting phenolic resin.
[0078] The modified thermosetting phenolic resin was then placed in a mold of a flat vulcanizer and cured by stepwise heating: 135°C for 2h, 150°C for 2.5h, and 175°C for 3.5h to crosslink and cure the modified thermosetting phenolic resin. Figure 5 The impact test piece was tested according to GB / T2567-2008 Test Method for Performance of Resin Castings, and the impact strength was 7.12KJ·m -2 , the fracture morphology is as follows Figure 6 As shown in the figure, the porosity of the specimens is greatly reduced.
[0079] Example 4
[0080] Preparation of impact test pieces
[0081] In parts by weight, 100 parts of phenolic resin, 45 parts of liquid nitrile rubber, 40wt% acrylonitrile content; 20 parts of cerium dioxide, particle size 10μm, 25 parts of zirconium dioxide, particle size 20nm. The phenolic resin and liquid nitrile rubber are placed in a 130°C oven respectively, the phenolic resin is heated to a viscosity of 300cp, and the liquid nitrile rubber is heated to a viscosity of 500cp. The liquid rubber is added to the phenolic resin and mixed evenly, and cerium dioxide and zirconium dioxide particles are gradually added, and mixed using a high-speed homogenizing and dispersing emulsifier (12000rpm), stirred for 15min, and then stirred in an oil bath (140°C) for 75min (700rpm) to obtain a modified thermosetting phenolic resin.
[0082] Then the modified thermosetting phenolic resin is placed in the mold of a flat vulcanizer and cured by stepwise heating: 130°C for 1.5h, 150°C for 2h, and 170°C for 3h, so that the modified thermosetting phenolic resin is cross-linked and cured. Figure 7 The impact test piece was tested according to GB / T2567-2008 Test Method for Performance of Resin Castings, and the impact strength was 6.86KJ·m -2 , the fracture morphology is as follows Figure 8As shown in the figure, the porosity of the specimen is greatly reduced and the performance is greatly improved.
[0083] Example 5
[0084] Preparation of tensile specimens
[0085] In parts by weight, 200 parts of phenolic resin, 60 parts of liquid nitrile rubber, 40wt% acrylonitrile content; 40 parts of cerium dioxide, 50μm particle size, 20 parts of silicon dioxide, 80nm particle size. The phenolic resin and liquid nitrile rubber are placed in a 140°C oven respectively, the phenolic resin is heated to a viscosity of 150cp, and the liquid nitrile rubber is heated to a viscosity of 850cp. The liquid rubber is added to the phenolic resin and mixed evenly, cerium dioxide and silicon dioxide particles are gradually added, mixed using a high-speed homogenizing and dispersing emulsifier (15000rpm), stirred for 25min, and then stirred in an oil bath (145°C) for 50min (550rpm) to obtain a modified thermosetting phenolic resin.
[0086] Then the modified thermosetting phenolic resin is placed in the mold of a flat vulcanizer and cured by step-wise heating: 130°C for 1h, 155°C for 1.5h, and 175°C for 2.5h to crosslink and cure the modified thermosetting phenolic resin to obtain a tensile specimen. Fig. 9 The tensile test piece was tested according to GB / T2567-2008 Test Method for Performance of Cast Resin, and the tensile strength was 32.98MPa, the elongation at break was 2.98-3.65%, and the fracture morphology was as shown in Fig.10 As shown in the figure, the porosity of the specimens is greatly reduced.
[0087] Example 6
[0088] Preparation of compression specimens
[0089] In parts by weight, 50 parts of phenolic resin, 15 parts of liquid nitrile rubber, 40wt% acrylonitrile content; 10 parts of cerium dioxide, 50μm particle size, 8 parts of silicon dioxide, 80nm particle size. The phenolic resin and liquid nitrile rubber are placed in a 130°C oven respectively, the phenolic resin is heated to a viscosity of 120cp, and the liquid nitrile rubber is heated to a viscosity of 900cp. The liquid rubber is added to the phenolic resin and mixed evenly, cerium dioxide and silicon dioxide particles are gradually added, mixed using a high-speed homogenizing and dispersing emulsifier (18000rpm), stirred for 30min, and then stirred in an oil bath (135°C) for 60min (600rpm) to obtain a modified thermosetting phenolic resin.
[0090] Then the modified thermosetting phenolic resin was placed in the mold of a flat vulcanizer and cured by step-wise heating: 110℃ for 1.5h, 140℃ for 1.5h, and 180℃ for 3h to crosslink and cure the modified thermosetting phenolic resin to obtain 99 compression test pieces. Fig.11 The compression specimens were tested according to GB / T2567-2008 Test Method for Performance of Resin Castings. The compression strength was 224.5MPa, the compression deformation was 7.56mm, and the fracture morphology was as follows: Fig.12 As shown in the figure, the porosity of the specimens is greatly reduced.
[0091] Comparative Example 1
[0092] Preparation of ordinary thermosetting phenolic resin impact specimens:
[0093] 150 parts of phenolic resin were selected. In an oven at 130°C, the phenolic resin was heated to 200 cp, stirred in an oil bath (140°C) for 75 min (600 rpm), and then the low-viscosity phenolic resin was placed in the mold of a flat vulcanizer. The temperature was raised step by step: 135°C for 1.5 h, 155°C for 2.5 h, and 175°C for 3 h to obtain a common thermosetting phenolic resin specimen, such as Fig.13 As shown. The impact strength is only 1.09KJ·m -2 There are a lot of tiny cracks on the fracture surface, such as Fig.14 As shown, the porosity is high and the performance is poor and cannot be used normally.
[0094] Comparative Example 2
[0095] Preparation of tensile specimens of ordinary thermosetting phenolic resin:
[0096] First, prepare the raw materials of phenolic resin. Select 100 parts of phenolic resin. Heat the phenolic resin to 100cp in an oven at 130℃, stir it in an oil bath (130℃) for 60min (600rpm), then place the low-viscosity phenolic resin in the mold of a flat vulcanizer, and heat it step by step: 110℃ for 1.5h, 150℃ for 2.5h, and 165℃ for 4h to obtain a common thermosetting phenolic resin specimen, such as Fig.15 As shown in the figure, the tensile strength is only 12.70MPa, the elongation at break is 0.82%, and there are a large number of tiny cracks on the fracture surface, such as Fig.16 As shown, the porosity is high and the performance is poor and cannot be used normally.
[0097] Comparative Example 3
[0098] Preparation of ordinary thermosetting phenolic resin compression specimens:
[0099] 100 parts of phenolic resin were selected. In an oven at 130°C, the phenolic resin was heated to 100 cp, stirred in an oil bath (130°C) for 60 min (600 rpm), and then the low-viscosity phenolic resin was placed in the mold of a flat vulcanizer. The temperature was raised step by step: 120°C for 2 h, 160°C for 1.5 h, and 180°C for 2 h to obtain a common thermosetting phenolic resin specimen, such as Fig.17 The compression strength is 120MPa, the compression deformation is 1.46mm, and there are a large number of tiny cracks on the fracture surface, such as Fig.18 As shown, the porosity is high and the performance is poor and cannot be used normally.
[0100] Table 1 summarizes the performance of the impact test piece of modified phenolic resin prepared in Example 1, the tensile test piece prepared in Example 5, and the compression test piece prepared in Example 6 of the present invention, as well as the impact test piece, tensile test piece, and compression test piece of ordinary thermosetting phenolic resin prepared in Comparative Examples 1 to 3. Among them, the friction coefficient and the wear amount are the data of the embodiment and comparative example 1, respectively.
[0101] Friction and wear test: The test conditions are reciprocating friction, reciprocating distance 10mm, speed 100mm / s, grinding ball diameter 6mm, material GCr15 steel ball, test load 50N, test time 30min. Three samples are tested in each group. The wear amount is tested by weighing the test piece before and after friction. Among them, the friction coefficient of comparative example 1 is 0.56, 0.58, and 0.62, and the friction coefficient of embodiment 1 is 0.32, 0.36, and 0.41; the wear amount of comparative example 1 is 24.12%, 25.24%, and 27.26%, and the wear amount of embodiment 1 is 8.78%, 9.61%, and 10.01%.
[0102] Table 1 Performance comparison between high performance low porosity phenolic resin and common thermosetting phenolic resin
[0103] Ordinary thermosetting phenolic resin (PF-602) Modified phenolic resin of the present invention <![CDATA[Impact strength KJ·m -2 > 1.09 7.77 Tensile strength(MPa) 12.70 32.98 Bending strength(MPa) 37.00 43.50 Compression strength(MPa) 120.00 224.50 Elongation at break (%) 0.82 3.65 Compression deformation(mm) 1.46 7.56 Friction coefficient 0.58 0.36 Wear amount (%) 25.24 9.61
[0104] As can be seen from Table 1, compared with ordinary thermosetting phenolic resin, the mechanical properties of the modified phenolic resin prepared by the present invention are greatly improved, the tensile strength is increased by 159.68%, the flexural strength is increased by 17.57%, the impact strength is increased by 612.84%, the compressive strength is increased by 87.08%, the elongation at break is increased by 345.12%, and the compression deformation is increased by 110.59%; the porosity of the specimen is greatly reduced, and the excellent compressive and friction properties broaden its use, so that it can be applied to the directions of wear resistance and compression resistance.
[0105] Comparative Example 4
[0106] The amount of raw materials does not meet the requirements
[0107] Preparation of impact test pieces
[0108] In parts by weight, 100 parts of phenolic resin, 80 parts of liquid nitrile rubber, 40wt% acrylonitrile content; 15 parts of cerium dioxide, 50μm particle size, 10 parts of silicon dioxide, 80nm particle size. The phenolic resin and liquid nitrile rubber are placed in a 130°C oven respectively, the phenolic resin is heated to a viscosity of 100cp, and the liquid nitrile rubber is heated to a viscosity of 1000cp. The liquid rubber is added to the phenolic resin and mixed evenly, cerium dioxide and silicon dioxide particles are gradually added, mixed using a high-speed homogenizing and dispersing emulsifier (20000rpm), stirred for 20min, and then stirred in a 130°C oil bath for 60min (600rpm) to obtain a modified thermosetting phenolic resin.
[0109] Then the modified thermosetting phenolic resin is placed in the mold of a flat vulcanizer and cured by step-by-step heating: 130°C for 2h, 150°C for 2h, and 170°C for 2h to crosslink and cure the modified thermosetting phenolic resin to obtain an impact specimen. Fig.19 The morphology of the modified phenolic resin specimen is shown in Fig. 20 As shown, the surface is full of defects, there is no sign of crack extension, and the impact toughness value is only 1.06KJ·m -2 , the performance is poor and cannot be used normally.
[0110] Comparative Example 5
[0111] Omit rare earth oxides and rigid oxide fillers
[0112] Impact test piece
[0113] In parts by weight, there are 100 parts of phenolic resin, 80 parts of liquid nitrile rubber, and 40wt% acrylonitrile; the phenolic resin and liquid nitrile rubber are placed in a 130°C oven respectively, and the phenolic resin is heated to a viscosity of 200cp, and the liquid nitrile rubber is heated to a viscosity of 800cp. The liquid rubber is added to the phenolic resin and mixed evenly, and mixed using a high-speed homogenizing and dispersing emulsifier (20,000rpm), stirred for 30 minutes, and then stirred in an oil bath (130°C) for 60 minutes (600rpm), and then the modified thermosetting phenolic resin is placed in the mold of a flat vulcanizer, and the modified thermosetting phenolic resin is crosslinked and cured by stepwise heating: 130°C for 2h, 150°C for 2h, and 170°C for 2h. Fig.21 The morphology of the modified phenolic resin is shown in Fig. 22 As shown in the figure, the surface defects are reduced, there is no sign of crack extension, and the impact toughness value is only 2.05KJ·m -2 , the performance is poor and cannot be used normally.
[0114] It can be seen from the above embodiments and comparative examples that the present invention provides a modified thermosetting phenolic resin and a preparation method thereof. The modified thermosetting phenolic resin provided by the present invention has both high toughness and high overall mechanical strength, while the porosity is greatly reduced and the internal defects of the resin are few.
[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A modified thermosetting phenolic resin, characterized in that: The preparation method comprises the following raw materials, in parts by weight: 100 parts of thermosetting phenolic resin, 10 to 50 parts of liquid nitrile rubber, 1 to 30 parts of rare earth oxide and 1 to 30 parts of rigid oxide filler; The rigid oxide filler is one or more of silicon dioxide, titanium dioxide and zirconium dioxide.
2. The modified thermosetting phenolic resin according to claim 1, characterized in that: The liquid nitrile rubber is carboxyl-terminated liquid nitrile rubber, amine-terminated liquid nitrile rubber or vinyl-terminated liquid nitrile rubber.
3. The modified thermosetting phenolic resin according to claim 1 or 2, characterized in that: The acrylonitrile content of the liquid nitrile rubber is 5 to 50 wt %.
4. The modified thermosetting phenolic resin according to claim 1, characterized in that: The rare earth oxide is one or more of cerium oxide, praseodymium oxide, lanthanum oxide, europium oxide, lutetium oxide, ytterbium oxide, thulium oxide, dysprosium oxide, scandium oxide, yttrium oxide, erbium oxide, gadolinium oxide, holmium oxide, neodymium oxide, samarium oxide and terbium oxide.
5. The modified thermosetting phenolic resin according to claim 1 or 4, characterized in that: The particle size of the rare earth oxide is 10nm-100μm.
6. The modified thermosetting phenolic resin according to claim 1, characterized in that: The particle size of the rigid oxide filler is 10 nm to 10 μm.
7. The method for preparing the modified thermosetting phenolic resin according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: heating the thermosetting phenolic resin and the liquid nitrile rubber respectively to obtain the low-viscosity phenolic resin and the low-viscosity liquid nitrile rubber respectively; The low-viscosity phenolic resin, low-viscosity liquid nitrile rubber, rare earth oxide and rigid oxide filler are mixed to obtain the modified thermosetting phenolic resin.
8. The preparation method according to claim 7, characterized in that: The viscosity of the low-viscosity phenolic resin is 100-500 cp; the viscosity of the low-viscosity nitrile rubber is 500-1000 cp.
9. The preparation method according to claim 7, characterized in that: The mixing comprises: adding the low-viscosity liquid nitrile rubber into a low-viscosity phenolic resin, adding rare earth oxide and rigid oxide filler into the obtained mixed system, mixing using a high-speed homogenizing and dispersing emulsifier, and then stirring the obtained mixture at 100-150°C.
10. A modified thermosetting phenolic resin product, characterized in that: The modified thermosetting phenolic resin is obtained by curing the modified thermosetting phenolic resin according to any one of claims 1 to 6 or the modified thermosetting phenolic resin prepared by the preparation method according to any one of claims 7 to 9.
Citation Information
Cited By
Manufacturing process of soft abrasive disc
CN121403264A
